Experimental and Numerical Investigation of the Ground Shock Coupling Factor for Near-Surface Detonations - Timothy W. Shelton; John Q. Ehrgott; Ramon J. Moral; Michele Barbato (Shock and Vibration)
This paper presents the results of recent ground shock experiments conducted by the U.S. Army Engineer Research and Development Center to further investigate the adequacy of the coupling factor approach to shallow-buried or near-surface detonations. Comparisons between these recent experimental results and results of numerical simulations of the ground shock propagation in soil are presented. It was found that the coupling factor curve currently adopted in design of buried structures does not accurately represent the actual ground shock propagation in soil and that different coupling factor curves are needed for different physical quantities of interest in design. The results presented in this paper also suggest that the coupling factor curves are functions of several parameters in addition to the depth of burial and that numerical simulations can capture reasonably well the ground shock propagation of soil stresses and particle velocities.